Neonatal Seizures: Impact on Neurodevelopmental Outcomes - Kang, Seok Kyu; Kadam, Shilpa D. (Frontiers in Pediatrics, 2015)
Neonatal period is the most vulnerable time for the occurrence of seizures, and neonatal seizures often pose a clinical challenge both for their acute management and frequency of associated long-term co-morbidities. Etiologies of neonatal seizures are known to play a primary role in the AED responsiveness and the long-term sequelae. Recent studies have suggested that burden of acute recurrent seizures in neonates may also impact chronic outcomes independent of the etiology. However, not many studies, either clinical or pre-clinical, have addressed the long-term outcomes of neonatal seizures in an etiology-specific manner. In this review, we briefly review the available clinical and pre-clinical research for long-term outcomes following neonatal seizures. As the most frequent cause of acquired neonatal seizures, we focus on the studies evaluating long-term effects of HIE seizures with the goal to evaluate: 1) what parameters evaluated during acute stages of neonatal seizures can reliably be used to predict long-term outcomes?, and 2) what clinical and pre-clinical data are available to help determine the importance of etiology vs. seizure burdens for long-term sequelae.